Determine The Factors Affecting Product Quality Using FMEA Analysis: A Case Study in Al Zawraa State Company - Hayal, Alaa Farhan; Mahdi, Nidaa Saleh (Journal of Economics and Administrative Sciences, 2021)
The research aims to identify the factors that affect the quality of the product by using the Failure Mode and Effect Analysis (FMEA) tool and to suggest measures to reduce the deviations or defects in the production process. I used the case study approach to reach its goals, and the air filter product line was chosen in the air filters factory of Al-Zawraa General Company. The research sample was due to the emergence of many defects of different impact and the continuing demand for the product. I collected data and information from the factory records for two years (2018-2019) and used a scheme Pareto Fishbone Diagram as well as an FMEA tool to analyze data and generate results. Pareto diagram showed that there are (20) types of defects, (11) of which represent the most effective and (9) of them are the least effective. Stimulation (RPN = 160). Added value: Utilizing the (FMEA) tool in determining the factors that affect the quality of the product and determining the priority risks